FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS JULI KABUPATEN BIREUEN - Marlina Marlina (Jurnal Kesehatan dan Fisioterapi, 2021)
WHO and UNICEF recommend four important things to do, namely, giving breast milk to babies, giving breast milk exclusively from birth to 6 months of age, providing complementary foods with breast milk from the time the baby is 6 months old. up to 24 months Purpose : This study aimed to determine the factors associated with complementary feeding for infants aged 0-6 months in Juli Health Medical, Bireuen Regency. Method : The study was an analytic survey with a cross-sectional approach. Population was 153 mothers who had babies aged 0-6 months. The number of samples was 43 respondents. Data analysis used univariate and bivariate analyses using the chi-square test. Results : The results of the study based on the Chi-square test showed that the p-value = .010 < α-value = .05, the p-value = 0.016 < α-value = .05, the p-value = 0.000 < α = .05, Conclusion : The conclusion showed that there is a relationship between knowledge, husband's support and adequacy of breastfeeding with the provision of complementary foods in early at Juli Health medical in 2019. It is recommended that the Juli Health Medical and other health workers be more active in providing counseling to mothers who have babies 0-6 months, in order to provide complementary foods at the right timeKeywords: Early Complementary Feeding